Det åpne bibliotek Forskningsbibliotek i endring - Larsen, Håkon; Anderson, Astrid; Fagerlid, Cecilie; Straume, Ingerid (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
The stereotypical image of quiet, dusty rooms with hushing librarians does not ring true for contemporary research libraries. On the contrary, libraries are often at the forefront of technological development. As they open up to new activities and take on new responsibilities, patrons use libraries in new ways. Increased openness is a common denominator of these transitions. At the same time, there is an ambiguity attached to the celebration of "openness" as an indisputable good, an ambiguity resonating throughout this book.